Essentials of money, banking and financial institutions : with applications to the developing world - Andoh, Samuel K. (Samuel Kojo), 1952- (Lexington Books, 2014)
Essentials of Money, Banking and Financial Institutions builds on the essential concepts of money and banking and applies them in the context of developing countries. Frequent comparisons between developed and developing countries are made to enable students to make proper inferences about the efficacy of certain concepts.